Optimal stocking density for culturing tropical soil-dwelling earthworm, Pontoscolex corethrurus - Kok, H. Y.; Abd Aziz, Nor Azwady; Loh, Khye Er; Mustafa, Muskhazli; Zulkifli, Syaizwan Zahmir (Universiti Kebangsaan Malaysia, 2014)
The present study was carried out to determine the optimal stocking density for culturing tropical soil dwelling earthworm, Pontoscolex corethrurus. F1 generation earthworms were cultured in four different stocking densities of 1, 4, 7 and 10 worms per vessel, corresponding to field densities of 50, 200, 350 and 500 individuals per m2. Earthworms were kept under laboratory conditions (25±2°C and 25% moisture) for the 14 weeks study period. The results showed that at higher earthworm densities (>350 individuals per m2), the earthworm growth was slower and sexual maturation was delayed as compared with their counterparts in lower stocking density. With the high survival rate and parthenogenetic reproduction mode, P. corethrurus could potentially be used as tropical soil rehabilitation agent.